Anxiety and EFL speaking in Spanish compulsory and non-compulsory Secondary Education: A mixed-method study - Raquel Criado; Yáfar Mengual (Miscelánea: A Journal of English and American Studies, 2017)
This exploratory study aims to examine the relationship between language anxiety (LA) and the speaking skill for English as a Foreign Language in both Spanish Compulsory Secondary Education (CSE) and (Upper) Non-compulsory Secondary Education (NCSE). A sequential explanatory mixed-method study was implemented with two intact classes (18 CSE and 19 NCSE students).  In the quantitative phase the 37 students’ LA levels were measured through the Foreign Language Classroom Anxiety Scale (Horwitz, Horwitz and Cope 1986) to analyse their relationship with their school speaking test scores, using bivariate correlation and stepwise linear regression analyses. Quantitative results revealed an inverse relationship between the students’ LA levels and the test scores; the predictive power of course level and fear of negative evaluation in the test scores and the absence of an increase of LA as a function of the students’ course level. In the qualitative phase, follow-up interviews were conducted with four subjects whose quantitative results had revealed a non-isomorphic pattern in the relationship between LA and the test scores (high/low, low/high). The qualitative results corroborated the significance of fear of negative evaluation and made the prominence of other factors more visible. Several pedagogical implications are indicated.